Self-assessment of dental health status, behaviours and oral health risk factors among adolescents from public schools in Maputo City-Mozambique - Amália Issufo Mepatia; Neil Myburgh; Robert Barrie; Faheema Kimmie-Dhansay (BMC, 2024)
Abstract Self-assessment of dental health status may have an impact on the oral health behaviour of adolescents which could impact their oral health. Oral health has been linked to various medical health conditions, thus eliminating oral health diseases can improve general health. The present study aimed to assess the association between behaviours and risk factors (oral hygiene habits, sugar intake, urban/rural status) and negative self-perception of dental health status among adolescents attending public schools in Maputo City. Method An analytic cross-sectional study, conducted in three Primary public schools from urban and peri-urban areas in Maputo City selected by convenience due to their geographic location was included. The size of the sample was 236 12-year-olds. Data was collected using a self-completion questionnaire designed by the World Health Organization (WHO). Chi-square tests or Fishers' Exact tests were used for associations. A simple and multiple logistic regression was used to determine the strength of these associations using backward elimination (p < 0.05). Results: The sample consisted of 221 adolescents, with 114 (51.6%) residing in urban areas and 107 (48.4%) in peri-urban areas. More than half of the participants (111 individuals) reported having a negative perception of their dental health. In the urban location, a higher percentage of participants had a "negative" perception of dental health (57.9%, n = 66), while in the peri-urban location, more participants perceived their dental health as "positive" (57.9%, n = 62). Participants residing in an urban setting were 82% more likely to have a negative perception of dental health (AOR = 1.82 [95% C.I.: 1.05 to 3.14]). Those who had experienced dental pain tended to report a higher proportion of negative dental perception (57.2%, n = 91), with 2.7 times more likely to report a negative perception of dental health (AOR = 2.72 [95% C.I.: 1.46 to 5.08]). The majority (n = 139; 63.2%) claimed to clean their teeth twice a day. Conclusion There was a higher negative perception of dental health in urban areas. The need to strengthen oral health promotion in urban schools is high since schools play such a significant role in oral health promotion.